السعودية و طاجيكستان.. مسيرة العلاقات والمصالح المشتركة - Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
The relations between the Tajik people and the world began a long time ago, and they are relations with ancient historical roots. They met for long periods under the banner of one state, since Islam entered the Central Asian region. | بدأت العلاقات بين الشعب الطاجيكي و العالم منذ زمن بعيد, و هي علاقات ذات جذور تاريخية قديمة, فقد اجتمعت لحقب طويلة تحت راية دولة واحدة, منذ دخول الاسلام منطقة آسيا الوسطى.